Depression Literacy and Its Relationship with Psychological Status among Patients with Type 2 Diabetes Mellitus at Indonesia: A Community Mental Health Perspective - Zainuddin; Mihrawaty S. Antu; Irmayanti Putri N (Universitas Muhammadiyah Palu, 2026)
The aim of this study was to determine the relationship between depression literacy and psychological status among T2DM patients in primary health care services in Indonesia, which are still limited. This study analyzed this relationship among T2DM patients at the Kabila Community Health Center, Bone Bolango Regency, Gorontalo. A cross-sectional design was applied to 74 T2DM patients (from a population of 292; Slovin's formula, e = 10%) recruited by random sampling in January 2025. Depression literacy was measured using the Depression Literacy Questionnaire (D-Lit; 18 valid items; Cronbach's alpha = 0.799) and psychological status with the General Health Questionnaire (GHQ-12; Likert 0-3; alpha = 0.648). Data were analyzed using Spearman correlation, Kruskal-Wallis, and the Holm-corrected Mann-Whitney test. The mean depression literacy score was 7.20 (SD = 2.63), with the majority at a moderate level (67.57%); The mean GHQ-12 score was 19.12 (SD = 4.51), with 93.24% showing mild to severe levels of stress. Depression literacy scores did not significantly correlate with stress scores (rho = -0.17; 95% CI -0.38 to 0.07; p = 0.156), but stress levels differed across literacy categories (rho = 7.49; p = 0.024): the low literacy group showed higher stress than the moderate literacy group (median 26.0 vs. 18.0; Holm p = 0.021). More severe stress levels alleviated patients with the lowest levels of depression literacy, thus supporting community-based stress screening and targeted depression literacy education as social interventions in primary care.